Implementation of Islamic Business Ethics in Brown Sugar Production Chain in West Otam Village, North Sulawesi - Mokodompit, Farras Azizah; Samad, Telsy Fratama Dewi; Niu, Fitria Ayu Lestari; Sumendap, Priscilia Christina (Maqrizi: Journal of Economics and Islamic Economics, 2025)
This study aims to analyze the implementation of Islamic business ethics principles in the production practices and transactions of buying and selling brown sugar in West Otam Village and its implications on the sustainability of producers' income. The research uses a qualitative method with a field study approach. Data were collected through participatory observation, semistructured interviews with producers, collectors, and consumers, and documentation, then analyzed using Miles and Huberman's interactive model with source triangulation techniques and techniques. The results of the study show that the economic practices of the people of West Otam Village have substantively reflected the main values of Islamic business ethics, especially honesty (shiddiq), mutual willingness (an-tarāḍin), and responsibility (mas'uliyah), even though the business actors do not understand these concepts formally. The heavy inconsistency of the product due to the use of traditional molds does not give rise to the element of gharar in a substantive way because it is mitigated through information disclosure and agreement between the manufacturer and the buyer. The quality integrity of products without chemical mixtures is proven to build consumer trust and loyalty, which contributes to the stability of producers' income. However, the study also found that some small producers have some bargaining position against collectors, indicating that distributive justice is not optimal. This study concludes that Islamic business ethics not only function as a normative guideline, but also as a rational economic strategy in supporting the sustainability of rural micro business income. Therefore, this study recommends strengthening sharia-based local economic institutions as well as simple standardization of production tools to improve the justice and economic sustainability of the community.